Information from Office of UNHCR: Movement of Refugees - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Myer Cohen; Office of United Nations High Commissioner for Refugees Information regarding arrival and departure of refugees in Austria and other countries on December 20, 1956. Notes contributions from Ethiopia and France.